Estudos genético-populacionais em Astyanax aff. Scabripinnis da região da Serra da Mantiqueira - Limeira, Daniel Meneguello (2018)
Genetic studies of natural populations have long been helping the scientific community and society in general to understand the evolution and conservation of both environments and communities. These studies have helped to define the boundary between species, and the concept of species, which is extremely important but sometimes arbitrary and quite variable among the various groups of living beings. In similar way, they help to know the status of conservation of populations in the wild and to understand how the anthropic activity or the natural evolution of the landscapes raises the risk of extinctions. In this sense, many researchers have considered the Astyanax scabripinnis species complex as a good model for evolutionary studies. These fish are known to inhabit headwaters streams, forming isolated populations with their own morphological, genetic and evolutionary characteristics. Aiming to deepen the knowledge about the genetic-population patterns of A. scabripinnis, six populations of the Serra da Mantiqueira region are have been selected, three belonging to the Sapucaí river basin, tributaries of the Grande river in the Upper Paraná basin, and three in the Paraíba do Sul basin. Using microsatellites based markers and mitochondrial DNA, we sought to know the intra and interpopulation genetic variability levels, to identify structure and migration patterns and bottleneck-population events. In addition, we sought to establish relationships between the geological evolution of the landscape, mainly in the higher regions of the Serra da Mantiqueira and the isolation and colonization patterns observed. Among the most relevant results, can be highlighted that the levels of genetic variability within the populations, when compared to other populations of Astyanax, are reasonably good. However, four of the populations had high levels of gene fixation suggesting the occurrence of inbreeding and two presented evidence of events of population bottlenecks, which draws attention to their conservation status. It was also possible to observe evident differences between two of the populations and the others, which allowed to infer the oldest separation of one and formation of the other through the colonization by individuals of varied populations, probably by anthropic action. The results showed that the population structure does not accompany the separation in two drainage basins and other factors of the formation of the Campos do Jordão plateau (where most of the populations are used), such as tectonic movements and drainage captures should be taken into account to understand the observed patterns. Finally, the hypothesis that best explains the structuring of the populations of Astyanax aff. scabripinnis observed is the colonization of the region from the Upper Paraná basin and dispersion or vicariance for the headwaters of the Paraíba do Sul basin.